Structural characterization and osteogenic bioactivities of a novel Humulus lupulus polysaccharide. Issue 1 (24th December 2019) - Chen, Xiaoxia; Li, Tianyu; Qing, Degang; Chen, Jun; Zhang, Qian; Yan, Chunyan
Abstract : The female flowers of Humulus lupulus are used in traditional Chinese medicine, but the bioactive ingredients underlying its benefits remain unclear. So, it is beneficial for treating diseases to screen out active polysaccharides from H. lupulus . Abstract : Humulus lupulus is a perennial climbing plant of the subfamily Cannabioideae native to the Northern Hemisphere. The primary use of H. lupulus is in the brewing industry, where it is an essential ingredient for imparting a unique flavor (bitterness and aroma) to beer. The female flowers of H. lupulus are also used in traditional Chinese medicine, but the biologically active ingredients underlying its benefits remain unclear. China is the largest producer and consumer of H. lupulus in Asia. Using the waste from the beer-brewing process of H. lupulus as raw materials, the biologically active polysaccharides can be screened. This is useful for the full utilization of H. lupulus, potentially leading to disease prevention and treatment. In this study, we isolated a homogeneous polysaccharide (HLP50-1) with a molecular weight of 49.13 kDa from female flowers of H. lupulus via a DEAE-Cellulose 52 anion exchange column and a Sephadex G-75 gel filtration column. Methylation, GC-MS, and NMR analyses revealed that the HLP50-1 comprised →4)-α-d -Glc p -(1→, →6)-α-d -Man p -(1→, →3)-α-l -Rha p -(1→, β-d -Glc p -(1→, α-l -Ara f -(1→, →4, 6)-2-OAc-β-d -Gal p -(1→, β-d -Gal p -(1→, →3, 6)-β-d -Glc p -(1→, →2, 3, 4)-α-d -Xyl p -(1→, →6)-α-d -Glc p -(1→, →3)-α-d -Gal p -(1→, →4)-α-d -Gal p -(1→. Advanced structural analysis showed that the HLP50-1 contained irregular fragments of different sizes and shapes with a smooth surface. The aggregates appeared be composed of accumulated crystals. Furthermore, the osteogenic activities of the HLP50-1 were evaluated via MC3T3-E1 cells in vitro . The results showed that 0.13 μM HLP50-1 led to outstanding proliferation, differentiation, and mineralization of the MC3T3-E1 cells. Therefore, HLP50-1 has osteogenic effects, and it may be a candidate for the treatment of osteoporosis. It has broad application prospects in functional foods, health-care products, and pharmaceuticals.